2011
DOI: 10.1002/adsc.201100064
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Indium‐Boron Amorphous Alloy Mediator for Barbier‐Type Carbonyl Allylation in Aqueous Medium

Abstract: A novel indium-boron (In-B) amorphous alloy was prepared by chemical reduction of indi-À ] in aqueous solution and was applied to the water-medium Barbier-type allylation reactions. A variety of allyl halides could be efficiently added to aldehydes or ketones in water. Additionally, the as-prepared In-B exhibits much higher activity than the commercial In powder and the crystallized In-B owing to the high surface area, the unique amorphous alloy structure, and the high electron density on the In active sites r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Li and coworkers reported that the In-B amorphous alloy showed higher activity than the In powder in allylation of benzaldehyde in water, and maintained a high selectivity of 98% (Scheme 15). 305 They further demonstrated that In-B is active for the Barbier-type allylation of substituted benzaldehydes and a number of allylic halides with selectivities Z 97% at conversions Z 94%. In Barbier-type allylation of acetophenone on In-B, allyl bromide showed similar allylation result to the expensive allylboronate, giving the 2-phenyl-4-penten-2-ol selectivity of 94% at the conversion of 90%.…”
Section: Fischer-tropsch Synthesis (Fts)mentioning
confidence: 98%
“…Li and coworkers reported that the In-B amorphous alloy showed higher activity than the In powder in allylation of benzaldehyde in water, and maintained a high selectivity of 98% (Scheme 15). 305 They further demonstrated that In-B is active for the Barbier-type allylation of substituted benzaldehydes and a number of allylic halides with selectivities Z 97% at conversions Z 94%. In Barbier-type allylation of acetophenone on In-B, allyl bromide showed similar allylation result to the expensive allylboronate, giving the 2-phenyl-4-penten-2-ol selectivity of 94% at the conversion of 90%.…”
Section: Fischer-tropsch Synthesis (Fts)mentioning
confidence: 98%
“…Recently, we reported the first synthesis of In-B amorphous alloy NPs by chemical reduction method. 47 The average particle size was about 8.5 nm (Fig. 8).…”
Section: Case Studies Of Metalsmentioning
confidence: 99%
“…The utilization of amorphous alloys as catalysts has gained the attention of many scientists, due to their discriminating states. For instance, it has been reported that amorphous alloys shows higher catalytic activities than crystalline alloys in the hydrogenation, oxidation, and alkylation reactions . According to these studies, the completely disordered atomic arrangement of amorphous alloys contributes significantly to the enhancement of the catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that amorphous alloys shows higher catalytic activities than crystalline alloys in the hydrogenation,o xidation,and alkylation reactions. [4][5][6][7][8][9][10][11][12][13][14] According to these studies, the completely disordered atomica rrangemento fa morphous alloys contributes significantly to the enhancement of the catalytic activities.H owever,f ew researchers have paid attention to the relationship between the catalytic properties and the structural changes that occur during the crystallization process of amorphousa lloys. Amorphous alloys transform into various transitional intermediates tates, such as precrystallizeda nd partly crystallized states upon heating.…”
Section: Introductionmentioning
confidence: 99%